2022
DOI: 10.1161/circulationaha.121.057001
|View full text |Cite
|
Sign up to set email alerts
|

SPARC, a Novel Regulator of Vascular Cell Function in Pulmonary Hypertension

Abstract: Background: Pulmonary hypertension (PH) is a life-threatening disease, characterized by excessive pulmonary vascular remodeling, leading to elevated pulmonary arterial pressure and right heart hypertrophy. PH can be caused by chronic hypoxia, leading to hyper-proliferation of pulmonary arterial smooth muscle cells (PASMC) and apoptosis-resistant pulmonary microvascular endothelial cells (PMVEC). Upon re-exposure to normoxia, chronic hypoxia-induced PH in mice is reversible. In this study, we aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…In addition, the population selected in the dataset for clinical pathological data statistics and survival prognosis analysis may exhibit regional or genetic differences and certain differences in human physique and living environment are likely to be present. Increases in the serum levels of SPARC may occur as part of biological functions and processes such as tumors and obesity; of note, SPARC expression levels were upregulated in the lung during hypoxia induction in a mouse model, and the hypoxia-inducible factor 2A signaling pathway induces SPARC expression, which in turn has an effect on proliferation and apoptosis of tumor cells in humans (59)(60)(61). It has also been indicated that the SPARC signaling pathway induces albumin-bound paclitaxel, which enhances initial chemoresistance of patients with lung cancer and this may also be used to optimize individual gene therapy regimens, which are important for mechanistic studies, animal models and clinical treatment evaluation in NSCLC (62).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the population selected in the dataset for clinical pathological data statistics and survival prognosis analysis may exhibit regional or genetic differences and certain differences in human physique and living environment are likely to be present. Increases in the serum levels of SPARC may occur as part of biological functions and processes such as tumors and obesity; of note, SPARC expression levels were upregulated in the lung during hypoxia induction in a mouse model, and the hypoxia-inducible factor 2A signaling pathway induces SPARC expression, which in turn has an effect on proliferation and apoptosis of tumor cells in humans (59)(60)(61). It has also been indicated that the SPARC signaling pathway induces albumin-bound paclitaxel, which enhances initial chemoresistance of patients with lung cancer and this may also be used to optimize individual gene therapy regimens, which are important for mechanistic studies, animal models and clinical treatment evaluation in NSCLC (62).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Sparc knockdown by Sparc-specific short-hairpin RNA improved hemodynamic and cardiac function in PH mice. 1 As stated by Jin et al, the pathophysiology between World Health Organization group 1 PH (PAH) and group 3 PH (PH caused by hypoxia and/or lung diseases) differs. Nevertheless, previous studies have shown that pharmacological approaches that are meanwhile approved for the treatment of patients with PAH prevented or alleviated PH in hypoxic animal models.…”
Section: In Responsementioning
confidence: 99%
“…In vivo, Sparc knockdown by Sparc -specific short-hairpin RNA improved hemodynamic and cardiac function in PH mice. 1…”
Section: In Responsementioning
confidence: 99%
“…the present study focused mainly on pulmonary vasculature and neglected secondary right-sided heart failure. 1 To the best of our knowledge, the exact role of SPARC has never been addressed in pathological right ventricular remodeling. SPARC has recently been reported to regulate E-cadherin protein expression and to be involved in endothelial to mesenchymal transition, 4 an essential process implicated in PH development and progression.…”
Section: To the Editormentioning
confidence: 99%